limit x2-4x+3divididox2-x-6
Soluções para a tarefa
Respondido por
0
Resposta:
P(x)=ax²+bx+c =(x-x')*(x-x'') ..x' e x' são as raízes
x^2-4x+3=0
x'=1
x''=3
x^2-4x+3= (x-1)*(x-3)
x^2-x-6 =0
x'=-2
x''=3
x²-4x-6=0
(x+2)*(x-3)
_________________________________
Lim (x²-4x+3)/(x²-x-6)
x-->3
Lim (x-3)*(x-1)/(x+2)*(x-3)
x-->3
Lim (x-1)/(x+2) = (3-1)/(3+2)=2/5 é a resposta
x-->3
Perguntas interessantes
Matemática,
10 meses atrás
Matemática,
10 meses atrás
Saúde,
1 ano atrás
Química,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás